The Prediction and Influential Factors of Violence in Male Schizophrenia Patients With Machine Learning Algorithms - Yu, Tao; Zhang, Xulai; Liu, Xiuyan; Xu, Chunyuan; Deng, Chenchen (Frontiers in Psychiatry, 2022)
Objective: Early to identify male schizophrenia patients with violence is important for the performance of targeted measures and closer monitoring, but it is difficult to use conventional risk factors. This study aimed to employ machine learning (ML) algorithms combined with routine data to predict violent behavior among male schizophrenia patients. Moreover, the identified best model was utilized to select the main influential factors for violence in schizophrenia. Method: We enrolled a total of 397 male schizophrenia patients and randomly stratified them into the training set and the testing set, in a 7:3 ratio. We used eight ML algorithms to develop the predictive models. The main variables as input features selected by the least absolute shrinkage and selection operator (LASSO) were integrated into prediction models for violence among male schizophrenia patients. In the training set, 10 × 10-fold cross-validation was conducted to tune parameters. In the testing set, we evaluated and compared the predictive performance of eight ML algorithms in terms of area under the curve (AUC) for the receiver operating characteristic curve. Results: Our results showed the prevalence of violence among male schizophrenia patients was 36.8%. Logistic regression (LR) with a ROC of 0.6161 had better prediction ability than that of other algorithms. The LR algorithm identified main risk factors for violent behavior in patients with schizophrenia, including lower education level [0.556(0.378-0.816)], having cigarette smoking [2.121(1.191-3.779)], higher positive syndrome [1.016(1.002-1.031)] and higher social disability screening schedule (SDSS) [1.081(1.026-1.139)]. Conclusions: Male schizophrenia individuals have a high rate of violent behavior. ML algorithms are useful in early identifying male schizophrenia patients with violence and helping clinicians take preventive measures.